Bifunctional ZSM-5/hydrotalcite composite for enhanced production of 5-hydroxymethylfurfural from glucose. (31st May 2019) - Subsadsana, Maliwan; Miyake, Koji; Ono, Kaito; Ota, Misaki; Hirota, Yuichiro; Nishiyama, Norikazu; Sansuk, Sira
Abstract : Over 65% yield of 5-hydroxymethylfurfural from glucose was obtained under mild condition by using ZSM-5/HT composite as acid/base bifunctional catalyst. Abstract : We describe herein the preparation of ZSM-5/hydrotalcite composites and their catalytic activity for the formation of 5-hydroxymethylfurfural (5-HMF) from glucose. The composites with high surface area and sufficiency in both acidity and basicity were achieved by the hydrothermal and dry gel methods, denoted as ZSM-5/HT-hydr and ZSM-5/HT-dg, respectively. Used as a combined solid acid–base catalyst in a biphasic H2 O/THF/NaCl system, the ZSM-5/HT composites showed excellent bifunctional catalytic activities since the base sites on HT promoted an isomerization of glucose to fructose, while the acid sites on ZSM-5 enhanced a successive dehydration of fructose to 5-HMF. Under the optimized reaction conditions, this catalytic process provided over 90% glucose conversion with >65% yield of 5-HMF at 150 °C for 120 min and 0.1 : 1 mass ratio of catalyst to glucose. Even through both ZSM-5/HT composites exhibited a comparable catalytic performance, ZSM-5/HT-hydr was more stable, selective, reusable, and preferable for one-pot synthesis of 5-HMF from glucose in the studied conditions.